2022
DOI: 10.3389/fgene.2022.831146
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Differentially Mutated Genes in Non-Muscle and Muscle-Invasive Bladder Cancer in the Chinese Population by Whole Exome Sequencing

Abstract: Objective: To characterize the spectra of mutations in non-muscle invasive bladder cancer (NMIBC) and muscle-invasive bladder cancer (MIBC) in the Chinese population to identify any mutational features and find potential therapeutic targets.Materials and methods: We collected fresh bladder tumor samples from NMIBC (n = 9) and MIBC patients (n = 11) along with adjacent normal bladder tissue specimen and peripheral blood sample. Using whole exome sequencing (WES), we analyzed the mutation spectra of those NMIBC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
(63 reference statements)
1
1
0
Order By: Relevance
“…Given the importance of early diagnosis and treatment, p53 overexpression may be considered a good indication for more aggressive treatment. In spite of these results from many peer studies in different places over the world and during a few decades indicating a prognostic role of p53 immunostaining, our results revealed no significant difference in the p53 expression in MIBC when compared to NMIBC, which comes consistent with few other previous studies including the study conducted by Toll and Epstein reported no statistically significant difference between the invasive and non-invasive bladder tumors concerning IHC staining of p53 [45,46]. Tian and Epstein also studied 26 cases of bladder urothelial carcinomas for p53 and Ki-67 immunohistochemical expression noting that only 2 cases showed a significant increase of p53 staining expression in the invasive compared with the non-invasive tumors [47].…”
Section: Discussionsupporting
confidence: 88%
“…Given the importance of early diagnosis and treatment, p53 overexpression may be considered a good indication for more aggressive treatment. In spite of these results from many peer studies in different places over the world and during a few decades indicating a prognostic role of p53 immunostaining, our results revealed no significant difference in the p53 expression in MIBC when compared to NMIBC, which comes consistent with few other previous studies including the study conducted by Toll and Epstein reported no statistically significant difference between the invasive and non-invasive bladder tumors concerning IHC staining of p53 [45,46]. Tian and Epstein also studied 26 cases of bladder urothelial carcinomas for p53 and Ki-67 immunohistochemical expression noting that only 2 cases showed a significant increase of p53 staining expression in the invasive compared with the non-invasive tumors [47].…”
Section: Discussionsupporting
confidence: 88%
“…Traditionally, acquisition of a cancerous genome requires tumor resection, quality control and sequencing or panel detection, which is time-consuming, labor-intensive and expensive 12 . Identification of the genomic features of a tumor has significance for treatment and the prognosis 13 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Since APOBEC3s can drive tumorigenesis through mutagenic and not mutagenic pathways, it could be beneficial to inhibit APOBEC3s in specific but likely numerous oncogenic contexts (Table 6 ). For example, APOBEC3 inhibitors could potentially prevent non-muscle invasive bladder cancer from progressing to muscle-invasive disease, which has a higher APOBEC3-induced mutation burden [ 1 , 200 ]. APOBEC3 inhibitors could also slow STING-dependent metastasis, especially in combination with emerging STING inhibitors [ 157 , 201 ].…”
Section: Clinical and Therapeutic Significance Of Apobec3s In Cancersmentioning
confidence: 99%